Synergy of rehabilitation for stress-related disorders and ARIs in school-age children under the war condition in Ukraine - I.O. Mityuryayeva-Kornijko; Ie.A. Burlaka; T.D. Klets; O.A. Panchenko; A.V. Kabantseva; E.S. Sukhodolska (Zdorovʹe Rebenka)
Background. A significant part of the children’s population of Ukraine suffers from stress-related disorders, which lead to serious complications and somatic diseases, including an increased incidence of acute respiratory pathology, and create a global economic problem in the field of health care. This is a challenge for pediatric practice and requires improvement and increasing the effectiveness of rehabilitation measures, development of comprehensive therapeutic approaches. The purpose of the study: to increase the effectiveness of the rehabilitation for stress-related disorders and acute respiratory infections (ARIs) in school-age children under the conditions of martial law in Ukraine by means of synergistic pharmacological correction with the inclusion of immunocorrective and sedative agents. Materials and methods. The study included 125 children aged 6–10 years who permanently lived in the territory of Ukraine (Kyiv, Kharkiv, Lviv, Dnipro, Zaporizhzhia, Odesa, Kropyvnytskyi, Vinnytsia, Kryvyi Rih, Zhytomyr, Cherkasy, Poltava, Sumy, Berdychiv, Romny, Bila Tserkva) during the previous year. The study was carried out as part of the program of outpatient observation of children with various acute manifestations of ARIs against the background of stress damage to the nervous system due to the war in Ukraine, and taking naturopathic drugs with immunocorrective properties (scheme (1)): 1) affinity-purified antibodies to human interferon gamma (6 mg), histamine (6 mg) and CD4 (6 mg) — a mixture of homeopathic dilutions C12, C30 and C50; or in combination with a drug with a sedative effect (scheme (1+2)): 1) affinity-purified antibodies to human gamma interferon (6 mg), histamine (6 mg) and CD4 (6 mg) — a mixture of homeopathic dilutions C12, C30 and C50; 2) affinity-purified antibodies to brain-specific protein S100 (3 mg) — a mixture of homeopathic dilutions C12, C30 and C50. Statistical processing of the results was carried out using GraphPad Prism 9.0 Software for Windows (USA, San Diego, CA). Results. The synergistic therapeutic effect of the scheme (1+2) showed a significantly better impact on stress-related disorders — sleep disorders, post-traumatic stress disorder, stress-related disorders, quality of life. In addition, there was a more pronounced corrective and rehabilitative effect of the scheme (1+2) on the indicators of fever, duration of low fever, sore throat, runny nose, symptoms of bronchitis, and manifestations of respiratory infection, assessed according to the Wisconsin Questionnaire. Analysis of satisfaction with the treatment effect on the IMOS international scale during the observation period showed positive results and a high level of assessment by both doctors and parents. Conclusions. Thus, the synergy of rehabilitation for stress-related disorders and ARIs in school-age children under martial law in Ukraine with the use of immunocorrective and sedative agents has pronounced effect, both early and delayed, a high level of assessment by doctors and parents of children aged 6–10 years.